Analysis of Cause of Endodontic Failure of C-Shaped Root Canals. (25th November 2018) - Kim, Yemi; Lee, Donghee; Kim, Da-Vin; Kim, Sin-Young
Abstract : The purpose of this study was to analyze various characteristics and classification of C-shaped root canals and evaluate the causes of endodontic failure of C-shaped root canals by examining the resected root surface with an endodontic microscope and a scanning electron microscope (SEM). Forty-two teeth with C-shaped root canals were included in this study and had undergone intentional replantation surgery. Before surgery, periapical radiography and cone-beam computed tomography were taken. The root canal configuration was analyzed and classified according to Melton's classification at coronal and apical level. After injection of 1 : 100, 000 epinephrine with 2% lidocaine, the tooth was carefully extracted. After the root-end resection, the resected root surface was examined using an operating microscope and SEM. Mandibular second molars were most frequently involved teeth (90.4%). The most frequently observed root canal configurations were C1 at the coronal level (45.2%) and C3 at the apical 3 mm level (45.2%). The most common cause of failure for a C-shaped root canal treatment was a leaky canal (45.2%), followed by an isthmus (23.8%), missing canal, overfilling, and iatrogenic problems. In conclusion, C-shaped root canals were most frequently found in mandibular second molars. The most common cause of failure was a leaky canal and isthmus.